JUVENILE GASTROPODS FROM THE UPPER DEVONIAN CEPHALOPOD BEDS AND ADJACENT STRATA OF CENTRAL IRAN (Journal of Sciences, Islamic Republic of Iran)
Microgastropod fauna from the Upper Devonian Cephalopod Bed and overlying Lower Tournaisian strata of the original reference section of the Shishtu Formation have been examined. Twenty genera and one unknown genus have been identified. The original aragonite shells have been replaced either by pyrite or fluorapatite